ISG15 Functions as an Interferon-Mediated Antiviral Effector Early in the Murine Norovirus Life Cycle - Rodriguez, Marisela R. (American Society for Microbiology, 2014)
Human noroviruses (HuNoV) are the leading cause of nonbacterial gastroenteritis worldwide. Similar to HuNoV, murine noroviruses (MNV) are enteric pathogens spread via the fecal-oral route and have been isolated from numerous mouse facilities worldwide. Type I and type II interferons (IFN) restrict MNV-1 replication; however, the antiviral effectors impacting MNV-1 downstream of IFN signaling are largely unknown. Studies using dendritic cells, macrophages, and mice deficient in free and conjugated forms of interferon-stimulated gene 15 (ISG15) revealed that ISG15 conjugation contributes to protection against MNV-1 both in vitro and in vivo. ISG15 inhibited a step early in the viral life cycle upstream of viral genome transcription. Directly transfecting MNV-1 RNA into IFN-stimulated mouse embryonic fibroblasts (MEFs) and bone marrow-derived dendritic cells (BMDC) lacking ISG15 conjugates bypassed the antiviral activity of ISG15, further suggesting that ISG15 conjugates restrict the MNV-1 life cycle at the viral entry/uncoating step. These results identify ISG15 as the first type I IFN effector regulating MNV-1 infection both in vitro and in vivo and for the first time implicate the ISG15 pathway in the regulation of early stages of MNV-1 replication. IMPORTANCE Type I IFNs are important in controlling murine norovirus 1 (MNV-1) infections; however, the proteins induced by IFNs that restrict viral growth are largely unknown. This report reveals that interferon-stimulated gene 15 (ISG15) mitigates MNV-1 replication both in vitro and in vivo. In addition, it shows that ISG15 inhibits MNV-1 replication by targeting an early step in the viral life cycle, MNV-1 entry and/or uncoating. These results identify ISG15 as the first type I IFN effector regulating MNV-1 infection both in vitro and in vivo and for the first time implicate the ISG15 pathway in the regulation of viral entry/uncoating.